Religious Moderation Policy in Islamic Education during the Lukman Hakim Saifuddin Era - Rizky Firnanda; Ninda Faradhila; Aulia Nazar; Arif Wasiatul Wafa; Fikri Fathul Aziz; Adinda Puji Rahmawati; Rahmat Riduan; M. Rizki Alfareza (Jurnal Pendidikan Terapan, 2026)
This study aims to analyze the policy of religious moderation in Islamic education during the era of Lukman Hakim Saifuddin as Minister of Religious Affairs of the Republic of Indonesia. The study focuses on the formulation of religious moderation policies, their implementation in Islamic education institutions, and their contribution to strengthening moderate Islamic values. This research employed a qualitative approach with a policy analysis method. The primary data sources consisted of policy documents issued by the Ministry of Religious Affairs, including guidelines, regulations, and official documents related to religious moderation programs, supported by interviews with relevant stakeholders in Islamic education. Data were analyzed through content analysis by identifying policy objectives, implementation strategies, and their implications for Islamic education development. The findings indicate that religious moderation became a central direction of Islamic education policy during Lukman Hakim Saifuddin’s leadership. The policy was implemented through curriculum development, strengthening teachers’ understanding of moderation values, and integrating principles of tolerance, balance, and respect for diversity into Islamic education. However, implementation faced challenges, including differences in institutional readiness and varying interpretations of religious moderation among educational actors. This study implies that Islamic education policies need continuous strengthening through systematic implementation strategies, teacher capacity development, and institutional support to ensure that religious moderation becomes an integral part of Islamic education. This research contributes to the study of Islamic education policy by specifically examining the relationship between religious moderation policy formulation and its implementation during the Lukman Hakim Saifuddin era, providing a policy perspective on the development of moderate Islamic education in Indonesia.